2014
DOI: 10.1371/journal.pone.0083209
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Anal HPV Infection in High-Risk Men Attending a Sexually Transmitted Infection Clinic in Puerto Rico

Abstract: PurposeRecent studies in Puerto Rico have reported an increasing incidence of anal cancer in Puerto Rican men. The objective of this study was to determine the prevalence, genotype distribution and risk factors associated with anal HPV infection among men attending an STI clinic in Puerto Rico.MethodsWe conducted a cross-sectional study among 205 men 18 years and older. A comprehensive survey was administered that included a demographic and a behavioral assessment. Separate logistic regression models were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 13 publications
4
22
0
1
Order By: Relevance
“…These results are similar to studies from different geographic areas [7, 23]. However, Colon-Lopez et al detected mostly HPV-58, 31 and 51 in high-risk men attending a sexually transmitted infection clinic in Puerto Rico [25]. The different prevalence and distribution of anal HPV subtypes in different study populations is of interest since it might reflect different geographic distributions of HPV genotypes or heterogeneous host susceptibility to the pathogens.…”
Section: Discussionsupporting
confidence: 84%
“…These results are similar to studies from different geographic areas [7, 23]. However, Colon-Lopez et al detected mostly HPV-58, 31 and 51 in high-risk men attending a sexually transmitted infection clinic in Puerto Rico [25]. The different prevalence and distribution of anal HPV subtypes in different study populations is of interest since it might reflect different geographic distributions of HPV genotypes or heterogeneous host susceptibility to the pathogens.…”
Section: Discussionsupporting
confidence: 84%
“…In Russia, the adult HIV prevalence of 1.1% has been reported, with an increase in HIV distribution affecting heterosexuals . Although it has not yet formally proven that anal cancer screening programs will lead to a decline of anal cancer incidence, screening for anal cancer is recommended for all HIV‐infected men in the United States and some European countries (eg, Germany and Austria), regardless of their sexual orientation as the presence of any HPV type is more than three times as common among HIV‐positive as compared to HIV‐negative subjects …”
Section: Discussionmentioning
confidence: 99%
“…Men infected with human immunodeficiency virus (HIV) who have sex with men (MSM) are at increased risk of HPV infection and anal cancer and are at the focus of the research on anal HPV epidemiology. The only limited range of studies, most from the Americas (Brazil, Mexico, United States and Puerto‐Rico) and 1 from Asia (Korea), have reported on the detection of the HPV in the anal canal of HIV‐negative men practicing sex with women (MSW).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to consider conducting future qualitative studies targeting parents and children from different age-gender subgroups. Specifically, future efforts should focus among young men, where a wide area of research in Puerto Rico has shown a higher burden of HPV infection as well as HPV-related cancers (Colón-López et al 2015; Colón-López et al 2014; Colón-López et al 2013; Colón-López et al 2012; Colón-López et al 2010). …”
Section: Conclusion and Implications For Practicementioning
confidence: 99%